MANAGING ROLE CONFLICT: NEW CHALLENGES BEFORE WORKING WOMEN - Gowda, Krishne; Rao, Padmini (PEOPLE: International Journal of Social Sciences, 2018)
Modern, globalized society is characterized by successful attempts by women to gain gender equality in occupations enabled by a number of interventions: education, affirmative action and economic empowerment policies. Yet, large numbers of working women encounter conflict in performing dual roles of housework and paid-work. Their work life is a constant effort to strike a balance between domestic duties and paid-work related demands- both in rural and urban contexts. In India, caste, class, religion and region play a significant role in contributing to these conflicts.This paper looks at the role conflict situation of women working in three different sectors- Information Technology, Shopping Malls and Public Transport Department. This is based on an explorative study sponsored by the UGC, New Delhi and conducted in the city of Bengaluru.The findings of the study show many dimensions of women’s balancing act to manage dual roles. Contrary to expectations, these are positive and success oriented. Women were found to have greater problems in the work place alone which have more importance than child care and household responsibilities, which are increasingly being shared by the husband and parents-in-laws, with the economic status of the woman held valuable, adding to household income & social mobility of the family as a whole.Work related problems are dominant in the context of gender discrimination in promotions, wages/salary and work environment.The paper calls for wider discussion across scholars to arrive at a global gender policy on new dimensions of Role conflict and gender, keeping social security and sustainable livelihoods for vulnerable women (Tribal, Dalit and Muslim) in focus.